The Sounds of Softness. Designing Sound for Human-Soft Robot Interaction - Jørgensen, Jonas; Christiansen, Mads Bering (Frontiers in Robotics and AI, 2021)
In this article, we report on research and creative practice that explores the aesthetic interplay between movement and sound for soft robotics. Our inquiry seeks to interrogate what sound designs that might be aesthetically engaging and appropriate for soft robotic movement in a social human-robot interaction setting. We present the design of a soft sound-producing robot, SONŌ, made of pliable and expandable silicone and three sound designs made for this robot. The article comprises an articulation of the underlying design process as well as results from two empirical interaction experiments (N=66, N=60) conducted to evaluate the sound designs. The sound designs did not have statistically significant effects on people’s perception of the social attributes of two different soft robots. Qualitative results, however, indicate that the interpretations of the sound designs depend on robot type.